Inovasi Pelayanan Publik melalui Sistem Aplikasi Potensi Investasi (Siapi) di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Dumai - Maysara Maysara; Hasim Asari (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
Public service is the government's responsibility to its citizens as mandated by the 1945 Constitution. One government agency that provides public services is the Department of Investment and One Stop Integrated Service, Dumai City. Dumai City DPMPTSP is aggressively making innovations to improve services. The innovation in question is the Investment Potential Application (SIAPI) for ease of investing. The purpose of this study was to determine how public service innovation through SIAPI in DPMPTSP Dumai City and the inhibiting factors that affect the implementation of SIAPI. This research uses Rogers' innovation theory which has five indicators, namely relative advantage, compability, complexity, triability, and observability. The type of research used is qualitative research with a phenomenological approach. Collecting data required both primary data and secondary data from the results of interviews, observation, documentation, then analyzed so that conclusions are drawn from the research problem. The finding of this research is that innovation has not been going well. Factors that hinder the adoption of SIAPI are socialization, half implemented, HR and budget.